A Prime-Number/Uniform Angular Distribution Criterion for Blade Vibration Reduction - Li, Yong; Di, Yaao; Dong, Wenzheng; Yin, Fangxiang; Yin, Yihao; Han, Shanling (Engineering Transactions, 2026)
Currently, the vibration noise of casting cleaning equipment exceeds 95 dB, which not only shortens the equipment’s service life but also jeopardizes workers’ health. The primary cause lies in the resonance tendency resulting from an uneven distribution of blades in the shotblasting device. In this paper, a prime-number/uniform angular distribution criterion and a dynamic balance elimination relationship are established to minimize resonance coupling while accounting for the internal characteristics of the shot-blasting device and blade assembly. Subsequently, a shot-blasting device with seven prime-number angular front-curved blades was designed and fabricated, and the dynamic imbalance caused by  uneven blade distribution was compensated for by drilling. We employed the discrete element method to evaluate projectile velocity and stability. The results indicate that the shot velocity reaches a maximum of 75 m/s, with fluctuations within 4 m/s. After reaching 0.24 s, particles accelerated by the shot-blasting device achieve relative stability. Finally, vibration data acquired at a sampling frequency of 10 Ksps demonstrates that noise levels are reduced from 97 dB (traditional structure) to 93.3 dB (new model). This new criterion for shot-blasting machine models mitigates operational vibration while enhancing working conditions and improving overall stability and system reliability.